Bathroom Songs: Eve Kosofsky Sedgwick as a Poet - Edwards, Jason (punctum books, 2017)
Bathroom Songs: Eve Kosofsky Sedgwick as a Poet is the first book of essays to consider the poetry of one of the twentieth- and early twenty-first-century's most important literary, affect, and queer theorists. Acclaimed as one of the "truly innovative" poets of her generation by Maud Ellmann, Sedgwick's work as a poet is, perhaps, less well known, but is no less compelling than her ground-breaking trilogy of queer theoretical texts: Between Men: English Literature and Male Homosocial Desire, Epistemology of the Closet, and Tendencies.